Lung Function Profiles among Individuals with Nonmalignant Asbestos-related Disorders - Eun-Kee Park; Deborah H. Yates; Donald Wilson (Elsevier, 2014)
Background: Inhalation of asbestos fibers can lead to adverse health effects on the lungs. This study describes lung function profiles among individuals with nonmalignant asbestos-related disorders (ARDs). Methods: The study population was from the Workers' Compensation (Dust Diseases) Board of New South Wales, Sydney, Australia. Lung function measurements were conducted in males with asbestosis (n = 26), diffuse pleural thickening (DPT; n = 129), asbestosis and DPT (n = 14), pleural plaques only (n = 160) and also apparently healthy individuals with a history of asbestos exposure (n = 248). Standardized spirometric and single-breath diffusing capacity for carbon monoxide (DLCO) measurements were used. Results: Mean age [standard deviation (SD)] was 66.7 (10.3) years for all participants. Current and ex-smokers among all participants comprised about 9.0% and 54.8%, respectively. Median pack-years (SD) of smoking for ex- and current-smokers were 22.7 (19.9). Overall 222 participants (38.6%) and 139 participants (24.2%) had forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) measurements < 80% predicted, and 217 participants (37.7%) had FEV1/FVC results < 70%. A total of 249 individuals (43.8%) had DLco values < 80% predicted and only 75 (13.2%) had DLco/VA results < 80% predicted. A total of 147 participants (25.6%) had peak expiratory flow (PEF) measurements < 80% predicted. The presence of ARDs lowered the lung function measurements compared to those of healthy individuals exposed to asbestos. Conclusion: Lung function measurement differs in individuals with different ARDs. Monitoring of lung function among asbestos-exposed populations is a simple means of facilitating earlier interventions.